2020
DOI: 10.1155/2020/5209695
|View full text |Cite
|
Sign up to set email alerts
|

Effect of COL4A1 Expression on the Survival of Neoadjuvant Chemotherapy Breast Cancer Patients

Abstract: Optimal therapy for each patient depends on their subtype, anatomic cancer stage, gene status, and preferences. Neoadjuvant chemotherapy-treated tumors have shown attenuated tumor growth, but the therapy cannot completely reduce tumor cell dissemination to blood stream and distant metastasis. Though it has been indicated that the protein of the collagen type IV alpha 1 (COL4A1) gene is induced by p53 to inhibit angiogenesis and tumorigenic activity in cancer cells, its prognostic significance in breast cancer … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 23 publications
2
6
0
Order By: Relevance
“…The results indicated that the expression levels of COL4A1 in glioma tissues were significantly higher than those in normal brain tissues. This is supported by previous reports that COL4A1 expression is increased in malignant tumors (16,24,25,28). For instance, COL4A1 expression is also increased in numerous types of malignant tumor tissue (such as esophageal squamous cell carcinoma, renal cell carcinoma, urothelial carcinoma of the bladder and breast cancer) and has an important impact on the occurrence and development of cancer (16,20,24,28).…”
Section: Discussionsupporting
confidence: 85%
See 2 more Smart Citations
“…The results indicated that the expression levels of COL4A1 in glioma tissues were significantly higher than those in normal brain tissues. This is supported by previous reports that COL4A1 expression is increased in malignant tumors (16,24,25,28). For instance, COL4A1 expression is also increased in numerous types of malignant tumor tissue (such as esophageal squamous cell carcinoma, renal cell carcinoma, urothelial carcinoma of the bladder and breast cancer) and has an important impact on the occurrence and development of cancer (16,20,24,28).…”
Section: Discussionsupporting
confidence: 85%
“…This is supported by previous reports that COL4A1 expression is increased in malignant tumors (16,24,25,28). For instance, COL4A1 expression is also increased in numerous types of malignant tumor tissue (such as esophageal squamous cell carcinoma, renal cell carcinoma, urothelial carcinoma of the bladder and breast cancer) and has an important impact on the occurrence and development of cancer (16,20,24,28). Of note, COL4A1 has also been reported to be increased in LGG.…”
Section: Discussionsupporting
confidence: 83%
See 1 more Smart Citation
“…Sayyad et al demonstrated the role of Sdc1 in promoting brain metastasis in BC [ 36 ]. Several studies have demonstrated that COL4A1 expression could be used as a biomarker for superior prognosis in BC patients receiving neoadjuvant chemotherapy [ 37 ], while epigallocatechin-3-gallate (EGCG) exerted antitumor effects by restoring nine key genes, including COL4A1, in myeloid-derived suppressor cells (MDSCs) [ 37 ]. TGF β 1-activated cancer-associated fibroblasts (CAFs) promote BC growth and metastasis in part through autophagy [ 38 ].…”
Section: Discussionmentioning
confidence: 99%
“…Collagen type IV α1 chain (COL4A1), a type of collagen that belongs to the type IV collagen family, is a key component of the basement membrane and several studies have found that it acts as a cancer-promoting factor in several types of cancer (9)(10)(11)(12). Recent studies have found that COL4A1 is abnormally expressed in invasive ductal carcinoma of breast and bladder tumors and is associated with tumor invasion and metastasis (13,14). Furthermore, COL4A1 is reported to be upregulated in patients with OSCC (15).…”
Section: Introductionmentioning
confidence: 99%